Emotionen und Selbstwirksamkeit von angehenden Lehrkräften des Faches Musik. Eine Analyse der wechselseitigen Beziehung - Fiedler, Daniel; Frenzel, Anne C.; Hasselhorn, Johannes (45. Jahresband des Arbeitskreises Musikpädagogische Forschung, 2024)
Teachers’ emotions and self-efficacy are related to teachers’ instructional practices, relationships with students, and students’ academic outcomes, as well as contribut- ing to teachers’ professional well-being and job satisfaction. However, despite these clear findings, the relationship between these two constructs has hardly been re- searched in pre-service teachers, particularly in music education. The present study aimed to test the reliability of the adapted measures of emotions and self-efficacy in pre-service music teachers and to examine the theoretically and empirically as- sumed reciprocal relationship between these two constructs. The sample consisted of 71 pre-service teachers, and the data comprised self-reports on three discrete emotions and six dimensions of self-efficacy in teaching music. The reliability of the adapted measures was acceptable to good. The results of the correlational analy- sis supported the assumed linear relationships, suggesting that pre-service music teachers’ music teaching self-efficacy is positively linked with their anticipated en- joyment and negatively linked with their anticipated anxiety and ange